1992
DOI: 10.1021/es50002a601
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Suwannee River Fulvic Acid with Chloramine: Characterization of Products via 15N NMR

Abstract: ~~~~~ ~ rn Suwannee River fulvic acid was reacted with aqueous solutions of 15N-labeled chloramine and 15N-labeled ammonia. INEPT 15N-NMR spectra of the lyophilized products from both reactions exhibit major resonances between 90 and 120 ppm, denoting the formation of amides, enaminones, and/or aminoquinones. The striking similarity between spectra suggests that the observed N moieties result from reactions between fulvic acid and ammonia, an expected coproduct from the chlorination of the fulvic acid by Chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…30 Several studies reported previously the incorporation of nitrogen in the form of amines into organic matter in the presence of chloramines. 31,32 Products P294 and P324 were likely formed in high amounts (i.e., peak area relative to the initial peak area of TMDL, A P /A 0,TMDL ≥ 1) and were stable in the absence of H 2 O 2 (Figure S39 A). In UV/H 2 O 2 / NH 2 Cl oxidation, P294 Degradation Pathway of TMDL in UV, UV/NH 2 Cl, and UV/H 2 O 2 /NH 2 Cl Oxidation.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…30 Several studies reported previously the incorporation of nitrogen in the form of amines into organic matter in the presence of chloramines. 31,32 Products P294 and P324 were likely formed in high amounts (i.e., peak area relative to the initial peak area of TMDL, A P /A 0,TMDL ≥ 1) and were stable in the absence of H 2 O 2 (Figure S39 A). In UV/H 2 O 2 / NH 2 Cl oxidation, P294 Degradation Pathway of TMDL in UV, UV/NH 2 Cl, and UV/H 2 O 2 /NH 2 Cl Oxidation.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…biological immobilization in humified, amorphous organic Nitrogen can be incorporated into organic matter either directly through chemical reactions or indirectly through microbial activity and subsequent decomposition of microbial biomass. Nuclear magnetic resonance (NMR) spectra have shown that chemical reactions occur between isotopically enriched ammonia and humic substances or model compounds and comprise an abundance of signals assigned to aromatic amines, indoles, pyrroles and other products (Preston et al, 1982;Ginwalla & Mikita, 1992;Thorn & Mikita, 1992). These reactions were all studied at pH values higher than are typical for soils, and under controlled laboratory conditions using materials rich in total N and of large I5N enrichment.…”
Section: Introductionmentioning
confidence: 99%
“…The second labeling methodology involves the use of 13 C-labeled reactants to follow the course of a complex reaction or association such as the interaction of pollutants with humic acids. (6)(7)(8)(9)22,23) The first structural evidence for the type of interaction of pollutants with humic substances was provided using 1 3 C and 15 N site specific labeling in combination with 13 C and 15 N NMR, respectively.…”
Section: Solution Nmrmentioning
confidence: 99%
“…Grinwalla et al (22) examined the reaction of Suwannee River fulvic acids with chloramine using solution 15 N NMR. They report, that while chloramine itself may not form nitrogen containing moieties with Suwannee River fulvic acid, under the conditions examined, the chlorination coproduct, ammonia, most certainly does.…”
Section: Solution 15 N Nmrmentioning
confidence: 99%